Análisis Sociolingüístico de Tabús y Eufemismos Dentro del Contexto Educativo en Estudiantes de Bachillerato de la Unidad Educativa “La Salle” Riobamba - Jarrín Castro, Santiago David (2026)
This research, entitled “Sociolinguistic Analysis of Taboos and Euphemisms Within the Educational Context in High School Students at the La Salle Educational Unit in Riobamba,” aimed to analyse, from a sociolinguistic perspective, the use of taboos and euphemisms among first-year high school students at the La Salle Educational Unit in Riobamba. The study employed a non-experimental design with a quantitative research approach. This approach made it possible to understand the frequency of use and functional performance of linguistic expressions related to ideas and realities that have become taboo, as well as their sociolinguistic conditioning. The research is descriptive because it examines and details the phenomenon thoroughly. It is also field research, as it was carried out directly with students in an educational environment. The population consisted of 960 students from the La Salle Educational Unit in Riobamba, from which a sample of 32 first-year high school students from class “B” was selected for the study. To gather information on the students’ use of taboos and euphemisms, a survey was applied. The instrument used was a questionnaire containing closed-ended questions related to the use of taboos and euphemisms within the educational context of first-year high school students in class “B.